FAAS determination of Cu, Fe, Zn, Pb, Cd in tea-leaves using suspension sampling with ultrasonic agitation - WENG Di; XIE Xiao-mei (浙江大学学报. 农业与生命科学版)
To determine the copper, iron, zinc, lead and cadmium content of tea-leaves, leaf samples were powdered and sieved after being hot-dried at (80±2)℃ for 4 hours. Then,5 mL 0.15% agar solution was added and mixed thoroughly with the samples by ultrasonic agitation. and the prepared suspension of sample was directly introduced to FAAS for determination. The results obtained by this method were consistent with those obtained by wet treatment method, Relative deviation of two methods is <±0.96%, the t-test show that no significant difference was found. The advantages of the present method is convenience, rapidity and accuracy.